A Huge Penile Fibroepithelial Polyp Treated with Partial Penectomy: A Case Report and Review of the Literature - Adel Alrabadi; Sohaib Alhamss; Yasmeen Z. Qwaider; Saddam Al Demour (Case Reports in Medicine)
Fibroepithelial polyps are benign tumors of mesodermal origin that usually arise on the surface of the skin and to a lesser extent in the urinary tract; however, their presence on the penis is extremely unusual. We report the case of a 73-year-old male with an extremely large broad-based penile fibroepithelial polyp (FEP) involving the penile shaft and glans penis associated with chronic condom catheter use and that was treated with partial penectomy. A review of the literature is included to highlight the rarity of this case. To the best of our knowledge, this is the largest mass of its kind to be reported on the penis.